2009
DOI: 10.1007/s12034-009-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of hydroxyl terminated polybutadiene with biologically active fluorescent molecule

Abstract: A biologically active molecule, 2-chloro-4,6-bis(dimethylamino)-1,3,5-triazine (CBDT), has been covalently attached at the terminal carbon atoms of the hydroxyl terminated polybutadiene (HTPB) backbone. The modification of HTPB backbone by CBDT molecule does not affect the unique physico-chemical properties such as fluidity, hydroxyl value and microstructure of the parent HTPB. The formation of hydrogen bonding between the terminal hydroxyl groups and the nitrogen atoms of triazine moiety is the driving force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We have developed an alternate synthetic method for the attachment of the CDT molecule to the HTPB polymer backbone which does not require the synthesis of CDT molecule. Cyanuric chloride (CYC) have covalently attached at the terminal carbon atoms of the HTPB polymer backbone (scheme 2) (Muralisankar et al 2009b). The modified HTPB (HTPB-CYC hereafter) has been further reacted with NaN 3 to get the azide substitution at the 3,5 position of the attached cyanuric chloride by replacing the chlorine from the CYC moiety (scheme 2).…”
Section: Functionalization Of Htpbmentioning
confidence: 99%
“…We have developed an alternate synthetic method for the attachment of the CDT molecule to the HTPB polymer backbone which does not require the synthesis of CDT molecule. Cyanuric chloride (CYC) have covalently attached at the terminal carbon atoms of the HTPB polymer backbone (scheme 2) (Muralisankar et al 2009b). The modified HTPB (HTPB-CYC hereafter) has been further reacted with NaN 3 to get the azide substitution at the 3,5 position of the attached cyanuric chloride by replacing the chlorine from the CYC moiety (scheme 2).…”
Section: Functionalization Of Htpbmentioning
confidence: 99%
“…Hydroxyl-terminated polybutadiene (HTPB) is a diol oligomeric viscous liquid which finds many applications, especially as a binder in solid rocket propellant. There are several methods, published by us and other groups, that modify the HTPB backbone with varieties of functionality to enhance the physical properties like energy output and thermal and mechanical strength of resulting PU obtained from HTPB and diisocyanate polymerization. Recently, we demonstrated that attachment of dinitrobenzene (DNB) to the terminal position of HTPB, called HTPB-DNB, has improved the physical properties, especially tensile properties, significantly owing to the formation of supramolecular hydrogen-bonding network fibrilar structure …”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyl-terminated polybutadiene (HTPB) and modified HTPB are important telechelic liquid rubbers that are widely used in the binder system of composite solid propellants. Because of its unique properties, such as hydrolytic stability, resistance to aqueous acids and bases, adhesion to a variety of substrates, high processability with high solid loading, low-temperature flexibility, electrical insulation properties, and high elongation with good elastic recovery, HTPB is widely used not only in propellant applications but also in other areas, such as membranes, adhesives, coating, sealants, newer materials, etc. The reactive functional groups in the terminated liquid rubber could also be applied to build ABA triblock copolymers, toughened resins, , elastomers, cross-linked elastomers, and supermolecular polymer gels. …”
Section: Introductionmentioning
confidence: 99%